MANFAAT MORINGA OLIEVERA.LAMK (KELOR) DALAM PERSPEKTIF AL QURAN - Yulianti, Eny (ULUL ALBAB Jurnal Studi Islam, 2009)
Moringa oleivem lamk, known as Moringa, is native to North India but is now found throughout the tropics. Moringa is also known as horseradish tree, drumstick tree and mother’s best friend. All Moringa food products have a very high nutritional value. Leaves rubbed against the temple can relieve headaches, to stop bleeding from a shallow cut, apply a poultice of fresh leaves. There is an anti-bacterial and anti-inflammatory effect when applied to wounds or insect bites. Extracts of leaves can be used against bacterial or fungal skin complaints. Leaf tea treats gastric ulcers and diarrhoea. Eating Moringa food products is good for those suffering from malnutrition due to the high protein and fibre content We can eat the leaves, especially young shoots, young pods, flowers, roots, and in some species even the bark. All of the parts of the tree can be used in a variety of ways. Moringa is full of nutrients and vitamins and is good in your food as well as in the food of your animals. Moringa helps to water purification and is a useful source of medicines. It provides lots of leafy material that is useful when using alley cropping systems.